2012
DOI: 10.1021/la3008415
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Domain Pixelation Patterns Imposed by E-beam Fabricated Substrates

Abstract: This work describes a technique for forming nanometer-scale pixilated lipid domains that are self-organized into geometric patterns residing on a square lattice. In this process, a lipid multibilayer stack is deposited onto a silica substrate patterned with a square lattice array of bumps, hemispherical on their sides, formed by electron beam lithography. Domain patterns are shown to be confined to the flat grid between the bumps and comprised of connected and individual domain pixels. Analysis of lattices of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…The out-of-plane curvature of each bump was 9.7±0.8 μm −1 as measured previously by atomic force microscopy. 19 This is well above the curvature threshold range necessary for sorting the stiffer L o phase lipid from softer L d phase lipid.12 Note that each pattern was imprinted multiple times into a PMMA-coated silicon wafer (Fig. S1) allowing for statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The out-of-plane curvature of each bump was 9.7±0.8 μm −1 as measured previously by atomic force microscopy. 19 This is well above the curvature threshold range necessary for sorting the stiffer L o phase lipid from softer L d phase lipid.12 Note that each pattern was imprinted multiple times into a PMMA-coated silicon wafer (Fig. S1) allowing for statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, without walls, we showed in previous work that the initial L o area fraction supported by the same curvature lattice was significantly less, 0.43 ± 0.01. 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…64 We showed that nanometer-scale lipid sorting patterns are possible using an underlying substrate containing a square lattice pattern of hemispherical features, formed by standard e-beam lithography of a poly(methyl methacrylate) (PMMA) layer on silica. 65 The high-bending modulus (~6×10 -19 J) 66 A variety of methods have been developed to attach functional molecules to lipid headgroups. These include covalent bonding 68 and linkers such as single-stranded DNA, 69 biotin, 70 and glycan-phosphatidyl inositol.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the case of SPBs, micropatterning techniques have been applied to generate arrayed patches of L o and L d phases in the model membranes. [11][12][13][14][15][16] For example, Yoon et al accumulated L o and L d phases on a silicon substrate by locally modulating the surface curvatures. L o and L d phases were enriched on the at and corrugated surfaces, respectively, due to the difference in bending energy.…”
Section: Introductionmentioning
confidence: 99%